Pengaruh Penggunaan Bioatraktan dan Perbedaan Ketinggian Perangkap terhadap Jumlah Tangkapan Lalat Buah (Diptera: Tephritidae) pada Tanaman Jambu Kristal (Psidium guajava L.) - Farrah Azzahra Yulfitriandi; Hery Haryanto; Suprayanti Martia Dewi (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Crystal guava is a fruit commodity with high economic value, with characteristics of crispy flesh, and few seeds, so it is widely cultivated by the people of Indonesia. West Nusa Tenggara Province, especially West Lombok Regency, is the largest producer of crystal guava. However, the potential for losses in this cultivation is quite high, one of which is caused by fruit fly attacks. This study aims to determine the effects of bioattractant types and trap height on fruit fly catch rates, as well as knowing the species of fruit flies caught. This research was conducted at Labuapi Agro-tourism, West Lombok Regency. The method used was experimental with a Factorial Randomized Group Design with 2 factors including the type of fruit extract (pineapple extract; mango extract; pineapple and mango combination extract, and methyl eugenol as control), and trap height (1; 1.5; and 2 meters). Data from the study were analyzed by ANOVA, and 5% BNJ further test. The results showed that the mango extract treatment at a height of 1.5 m had a more significant total catch of fruit flies and the number of female fruit flies captured compared to other types of treatment. The fruit fly species obtained were B. carambolae and B. dorsalis. The conclusion of this study is that mango extract and a trap height of 1.5 m significantly affect fruit fly capture and the extract can be an alternative recommendation for vegetable pesticides.